An introduction to computer graphics and creative 3-D environments - Blundell, Barry G. (London : Springer, 2008)
This book introduces the fundamentals of 2-D and 3-D computer graphics. It also examines a range of emerging, creative 3-D display technologies, including, among others, stereoscopic systems, immersive virtual reality, volumetric, and varifocal technologies.
Includes bibliographical references and index.
Keywords: Computer graphics; Three-dimensional display systems